Do Weak Institutions Prolong Crises? On the Identification, Characteristics, and Duration of Declines during Economic Slumps - Richard Bluhm; Denis de Crombrugghe; Adam Szirmai (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper defines economic slumps as sequences of structural breaks exhibiting a specific pattern. We identify 58 such episodes between 1950 and 2008 among 138 countries, and then examine the phases of decline and their duration. In some countries declines last extremely long, and we put several likely contributing factors to the test. We find evidence that weak institutions precede crises and, interestingly, positive reforms occur thereafter. Strong institutions shorten the duration of crises, ethnic cleavages do the reverse. However, the negative effects of ethnic cleavages are not insurmountable: an interaction effect suggests they can be offset by appropriate institutions.
Keywords: O43; O11; C41; F43; 330; economic slumps; crises; institutions; structural breaks; duration analysis